Clinical Experience with a Pasteurised Human Plasma Concentrate in Factor XIII Deficiency - Daly, Helena M; Haddon, M E (Thrombosis and Haemostasis, 1988)
A three-day-old infant presented with umbilical haemorrhage. Factor XIII deficiency was diagnosed. When one month old she commenced prophylactic injections of pasteurised factor XIII concentrate of human plasma origin. During two and a half years treatment there were no haemorrhagic episodes and factor XIII concentrate was well tolerated. Satisfactory post infusion factor XIII levels were achieved. Three transient elevations of aspartate transaminase occurred, the cause of which has not been established. There was no evidence of transmission of hepatitis or H.I.V. infection. A brother, born one year later, is also affected and commenced prophylactic therapy with the same factor XIII concentrate. Experience in these two infants suggests the product is efficacious.
Keywords: Factor XIII deficiency; Pasteurised concentrate